Religious Commitment and Attitudes of Gen-Z Women towards Polygamy: A Socio-Fiqh Transformative Review - Adiputra, Fadhil Hisyam; Setyawan, Edy (Al-Risalah, 2026)
Polygamy is a complex issue that often draws pros and cons in Muslim societies. The perspective of the younger generation of women, Gen-Z, towards this practice is important to examine because they are at the intersection of Islamic values and global influences through digital media. The purpose of this study is to analyse fiqh perspectives through the correlation between religious commitment and acceptance of polygamy among Gen-Z Muslim women, and to explore the sociological and religious factors that shape these attitudes. This research uses a mixed method approach with Explanatory Sequential design, starting from quantitative data collection through questionnaires to 111 respondents, followed by qualitative interviews. Quantitative analysis was conducted using correlation analysis test, while qualitative data was analysed thematically. The results showed a positive but weak correlation (ρ = 0.333) between religious commitment and attitudes towards polygamy. A total of 85.6% of respondents rejected polygamy, 9.9% accepted it, and 4.5% were neutral. Rejection was based on fear of injustice, emotional burden, and bad family experiences. Acceptance was driven by a textual understanding of religion, with conditions of justice and the first wife's permission. From a fiqh perspective, around 80% of polygamy practices in the sample were classified as makruh to haram due to lack of justice, financial unpreparedness and psychological impact. Only 20% are considered shar'i and socially permissible, such as in cases of infertility or honest agreement between spouses